Adhesive member, optical film having adhesive member, display system, display body or manufacturing method of display body

The adhesive member with controlled surface cleanliness and charge minimization addresses visibility issues in VR goggles by reducing foreign matter and charge accumulation, thereby improving image quality.

JP2025044447APending Publication Date: 2025-04-02NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023152014
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing VR goggles suffer from visibility issues due to the presence of foreign matter and charge accumulation on adhesive layers, leading to image display defects.

Method used

An adhesive member with a specific surface cleanliness and charge control, achieved by minimizing foreign matter particles and charge on the adhesive layer, optionally incorporating a conductive layer and antistatic agents, is used in VR goggles to prevent image defects.

Benefits of technology

The adhesive member significantly reduces foreign matter adhesion and charge accumulation, enhancing the visibility and reducing image display defects in VR goggles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044447000001_ABST
    Figure 2025044447000001_ABST
Patent Text Reader

Abstract

To provide an adhesive member capable of contributing to an improvement of visibility in a VR goggle.SOLUTION: An adhesive member includes an adhesive layer, and a release liner arranged at least on one side of the adhesive layer. When the release liner is removed from the adhesive member under an environment of class 10000 stipulated by US Federal Standard 209D, a number of foreign matters on a surface of the adhesive layer within a range of 20 mm angle is 12 or less. The adhesive member is used being laminated on a member composing a VR goggle.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive member, an optical film with an adhesive member, a display system, a display body, or a method for manufacturing a display body. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices), are rapidly becoming widespread. In image display devices, optical members such as polarizing members and phase difference members are generally used to realize image display and to improve the performance of the image display (see, for example, Patent Document 1).

[0003] In recent years, new applications for image display devices have been developed. For example, goggles with displays (VR goggles) for realizing Virtual Reality (VR) have begun to be commercialized. As VR goggles are being considered for use in a variety of situations, there is a demand for improvements in their visibility. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-103286 A Summary of the Invention [Problem to be solved by the invention]

[0005] A primary object of the present invention is to provide an adhesive member that can contribute to improving the visibility of VR goggles. [Means for solving the problem]

[0006] 1. An adhesive member according to an embodiment of the present invention is an adhesive member comprising an adhesive layer and a release liner disposed on at least one side of the adhesive layer, wherein when the release liner is peeled off from the adhesive member in a Class 10,000 environment defined by Federal Standard 209D, the number of foreign matter particles on the surface of the adhesive layer is 12 or less within a 20 mm square area, and the adhesive member is used by being laminated to components constituting VR goggles. 2. In the pressure-sensitive adhesive member described in 1 above, the amount of charge on the surface of the pressure-sensitive adhesive layer when the release liner is peeled off in an environment of a temperature of 23° C. and a humidity of 55% Rh may be less than 4.0 kV. 3. The pressure-sensitive adhesive member according to 1 or 2 above may further include a conductive layer, in which the conductive layer, the pressure-sensitive adhesive layer, and the release liner are disposed in this order. 4. In the pressure-sensitive adhesive member according to any one of the above items 1 to 3, the pressure-sensitive adhesive layer may contain an antistatic agent. 5 to 6. In the pressure-sensitive adhesive member according to any one of the above 1 to 4, the release liner may contain an antistatic agent. 7. In the pressure-sensitive adhesive member according to item 3 above, the conductive layer may contain an antistatic agent. 8. In the pressure-sensitive adhesive member according to the above item 4, the antistatic material may be an ionic liquid. 9. An optical film with an adhesive member according to an embodiment of the present invention comprises the adhesive member described in any one of 1 to 8 above. 10. A display system according to an embodiment of the present invention is a display system that displays an image to a user, comprising: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflecting section arranged in front of the display element and including a reflective polarizing member and reflecting the light emitted from the display element; a first lens section arranged on the optical path between the display element and the reflecting section; a half mirror arranged between the display element and the first lens section, transmitting the light emitted from the display element and reflecting the light reflected by the reflecting section towards the reflecting section; a first λ / 4 member arranged on the optical path between the display element and the half mirror; and a second λ / 4 member arranged on the optical path between the half mirror and the reflecting section, and comprising the optical film with adhesive member described in 9 above. 11. In the display system as described in 10 above, the display element may include the above-mentioned optical film with adhesive member. 12. A display according to an embodiment of the present invention comprises the display system according to 10 or 11 above. 13. A method for manufacturing a display according to an embodiment of the present invention is a method for manufacturing a display comprising the display system according to 10 or 11 above. 14. The method for producing a display as described in 13 above may include the step of adhering the optical film with adhesive member as described in 9 above. Effect of the Invention

[0007] According to an embodiment of the present invention, an adhesive member that can contribute to improving the visibility of VR goggles can be provided. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view of an adhesive member according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of an adhesive member according to an embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a general configuration of an example of a display system for VR goggles. [Figure 4]1 is a schematic cross-sectional view of an optical film with a pressure-sensitive adhesive member according to one embodiment of the present invention. [Diagram 5] 1 is a schematic cross-sectional view of a lens with an adhesive member according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but these are merely examples and do not limit the interpretation of the present invention. In addition, duplicate descriptions of the drawings may be omitted.

[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0011] A. Adhesive material 1 is a schematic cross-sectional view of a pressure-sensitive adhesive member according to an embodiment of the present invention. The pressure-sensitive adhesive member 100 according to the embodiment of the present invention comprises a pressure-sensitive adhesive layer 110 and a release liner 120 disposed on at least one surface of the pressure-sensitive adhesive layer 110.

[0012] 2 is a schematic cross-sectional view of an adhesive member according to another embodiment of the present invention. The adhesive member 100' according to the embodiment of the present invention comprises a conductive layer 130, an adhesive layer 110, and a release liner 120 in this order.

[0013] The adhesive member is used by being laminated on a member constituting the VR goggles.The adhesive member is used by being laminated directly on a member constituting the VR goggles.

[0014] In an embodiment of the present invention, when the release liner is peeled from the PSA member in a Class 10000 environment as defined by Federal Standard 209D, the number of foreign matter particles on the surface of the PSA layer is 12 or less within a 20 mm square area. The release liner may be peeled at a peel angle of 180° and a pulling speed of 300 mm / min. The number of adhering foreign matter particles is measured using an optical microscope 5 minutes after the release liner is peeled, and foreign matter with a major axis of 10 μm or more may be counted.

[0015] In the embodiment of the present invention, by controlling the number of foreign matter as described above, an adhesive member capable of preventing image display defects in VR goggles can be provided. In recent years, pancake lens systems and high-definition displays have been adopted for VR goggles, and image display defects caused by even smaller foreign matter may become a problem. In such cases, the adhesive member is particularly preferably used. By using the adhesive member, it is possible to prevent even minute foreign matter from being mixed in, and a display system with significantly fewer image display defects can be provided.

[0016] In a Class 10000 environment defined by Federal Standard 209D, the number of foreign objects on the surface of the adhesive layer when the release liner is peeled off from the adhesive member is preferably 10 or less, more preferably 8 or less, within a 20 mm square area. Within such a range, the above-mentioned effect becomes prominent. The fewer the number of foreign objects, the better, and the lower limit is, for example, 5 (preferably 2, more preferably 0).

[0017] In a Class 10,000 environment as defined by Federal Standard 209D, when the release liner is peeled off from the adhesive member, the number of foreign matter particles having a long diameter of 20 μm or less on the surface of the adhesive layer within a 20 mm square area is preferably 6 or less, more preferably 5 or less, even more preferably 3 or less, and particularly preferably 0.

[0018] The number of foreign matters can be controlled, for example, by adjusting the charge on the surface of the adhesive layer when the release liner is peeled off. In an environment of 23°C temperature and 55% Rh humidity, the charge on the surface of the adhesive layer when the release liner is peeled off is preferably less than 4.0 kV, more preferably less than 3.0 kV, even more preferably less than 2.0 kV, and particularly preferably less than 1.0 kV. The charge is the charge on the release surface of the release liner, and is measured at a distance of 35 mm from the adhesive layer 10 seconds after peeling the release liner at a peel angle of 180° and a pulling speed of 300 mm / min in an environment of 23°C temperature and 55% Rh humidity.

[0019] The amount of charge on the surface of the adhesive layer when the release liner is peeled off can be adjusted by imparting a predetermined electrical conductivity to one or more of the elements constituting the adhesive member. For example, it can be adjusted by imparting electrical conductivity to the adhesive layer and / or the release liner. Also, the amount of charge on the surface of the adhesive layer may be adjusted by providing a conductive layer as shown in FIG. 2. By providing a conductive layer, an adhesive member can be constructed without imparting electrical conductivity to the adhesive layer, which makes it easier to control the adhesive properties.

[0020] In one embodiment, the amount of charge can be adjusted by adding an antistatic agent to the pressure-sensitive adhesive layer. According to this embodiment, a pressure-sensitive adhesive member having a simple structure can be obtained.

[0021] In one embodiment, the amount of charge can be adjusted by adding an antistatic material to the release liner. According to this embodiment, an adhesive member having a simple structure can be obtained. In addition, the adhesive member can be constructed without imparting electrical conductivity to the adhesive layer, which makes it easy to control the adhesive properties.

[0022] The adhesive strength at 23° when the adhesive member is attached to alkali-free glass is preferably 1.0 to 12.0 N / 25 mm, more preferably 2.0 to 10.0 N / 25 mm. In this specification, the adhesive strength refers to the adhesive strength of the adhesive layer surface after the release liner is peeled off from the adhesive member, and is measured by a method in accordance with JIS Z 0237:2009 (lamination conditions: one round trip with a 2 kg roller, pulling speed: 300 mm / min, peel angle 180°).

[0023] B.Adhesive layer The thickness of the pressure-sensitive adhesive layer is preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm. From the viewpoint of smoothness, a thinner thickness is preferable.

[0024] The ISC value of the pressure-sensitive adhesive layer is, for example, 100 or less, preferably 50 or less. The ISC value can be an index of smoothness or unevenness. If the ISC value is within such a range, a pressure-sensitive adhesive member capable of realizing a display system with excellent visibility can be obtained. The lower limit of the ISC value of the pressure-sensitive adhesive layer is, for example, 10. The ISC value can be calculated by measuring an image projected onto a screen through the pressure-sensitive adhesive layer of interest with a CCD camera.

[0025] In one embodiment, the surface resistance value of the pressure-sensitive adhesive layer is preferably 1×10 12 Ω / □, more preferably less than 5×10 11 Ω / □, and more preferably less than 1×10 10 Within this range, the adhesive layer can be made to have favorable electrical conductivity, and an adhesive member capable of preventing image display defects in VR goggles can be provided. The adhesive layer having electrical conductivity can be obtained, for example, by adding an antistatic agent described below. When forming an adhesive layer having electrical conductivity, the lower limit of the surface resistance value of the adhesive layer is, for example, 1×10 8 The surface resistance is expressed in Ω / □. The method for measuring the surface resistance will be described later.

[0026] (Adhesive) The pressure-sensitive adhesive layer includes a pressure-sensitive adhesive. Examples of the pressure-sensitive adhesive include rubber-based pressure-sensitive adhesives, acrylic-based pressure-sensitive adhesives, silicone-based pressure-sensitive adhesives, urethane-based pressure-sensitive adhesives, vinyl alkyl ether-based pressure-sensitive adhesives, polyvinylpyrrolidone-based pressure-sensitive adhesives, polyacrylamide-based pressure-sensitive adhesives, and cellulose-based pressure-sensitive adhesives. In one embodiment, an acrylic pressure-sensitive adhesive is used.

[0027] The acrylic pressure-sensitive adhesive contains a (meth)acrylic polymer as a base polymer. The (meth)acrylic polymer contains structural units derived from an alkyl (meth)acrylate.

[0028] Examples of alkyl (meth)acrylates include alkyl (meth)acrylates having a straight-chain or branched alkyl group with a carbon number of 1 to 20 (more preferably 3 to 18, and particularly preferably 4 to 16). These can be used alone or in combination.

[0029] The content of the alkyl (meth)acrylate is preferably 65 parts by weight to 99.99 parts by weight, and more preferably 70 parts by weight to 99.9 parts by weight, based on 100 parts by weight of the (meth)acrylic polymer.

[0030] The (meth)acrylic polymer may contain a structural unit derived from another monomer (copolymerizable monomer) copolymerizable with the alkyl (meth)acrylate, if necessary. Examples of such a monomer include the following monomers. Aromatic ring-containing monomers: phenoxyethyl (meth)acrylate, benzyl (meth)acrylate; Carboxy group-containing monomers: for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), crotonic acid, etc.; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, citraconic acid, etc., and their anhydrides (maleic anhydride, itaconic anhydride, etc.); Hydroxyl group-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate; unsaturated alcohols such as vinyl alcohol and allyl alcohol; ether compounds such as 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether; Amino group-containing monomers: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, t-butylaminoethyl (meth)acrylate; Epoxy group-containing monomers: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether; Cyano group-containing monomers: for example acrylonitrile, methacrylonitrile; Keto group-containing monomers: for example, diacetone (meth)acrylamide, diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, vinyl acetoacetate; Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acryloylmorpholine; Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane; Isocyanate group-containing monomers: (meth)acryloyl isocyanate, 2-(meth)acryloyloxyethyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate; Silanes: 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltriethoxysilane, 10-acryloyloxydecyltriethoxysilane. These monomers may be used alone or in combination of two or more.

[0031] The content of the copolymerization monomer is preferably 0.01 to 35 parts by weight, and more preferably 2 to 25 parts by weight, based on 100 parts by weight of the (meth)acrylic polymer.

[0032] In one embodiment, the (meth)acrylic polymer contains a constituent unit derived from a hydroxyl group-containing monomer and / or a constituent unit derived from a carboxyl group-containing monomer. When the pressure-sensitive adhesive contains a crosslinking agent, these copolymerization monomers become reaction sites with the crosslinking agent. Hydroxyl group-containing monomers, carboxyl group-containing monomers, etc. are highly reactive with intermolecular crosslinking agents, and are therefore preferably used to improve the cohesiveness and heat resistance of the resulting pressure-sensitive adhesive layer.

[0033] The weight average molecular weight (Mw) of the (meth)acrylic polymer is, for example, 500,000 to 3,000,000, preferably 700,000 to 2,700,000, and more preferably 800,000 to 2,500,000. The weight average molecular weight is a value measured by GPC (gel permeation chromatography) and calculated in terms of polystyrene.

[0034] The (meth)acrylic polymer can be produced by appropriately selecting a known production method such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The obtained (meth)acrylic polymer may be any of a random copolymer, a block copolymer, a graft copolymer, etc.

[0035] The pressure-sensitive adhesive may contain any suitable additives as necessary, such as crosslinkers, crosslinking catalysts, tackifiers, plasticizers, pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, and antioxidants.

[0036] As the crosslinking agent, an organic crosslinking agent or a polyfunctional metal chelate can be used. Examples of the organic crosslinking agent include an isocyanate crosslinking agent, a peroxide crosslinking agent, an epoxy crosslinking agent, and an imine crosslinking agent. The polyfunctional metal chelate is a compound in which a polyvalent metal is covalently or coordinately bonded to an organic compound. Examples of the polyvalent metal atom include Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, and Ti. Examples of the atom in the organic compound that is covalently or coordinately bonded include an oxygen atom, and examples of the organic compound include an alkyl ester, an alcohol compound, a carboxylic acid compound, an ether compound, and a ketone compound.

[0037] The content of the crosslinking agent is preferably 3 parts by weight or less, more preferably 0.01 to 3 parts by weight, and even more preferably 0.02 to 2 parts by weight, based on 100 parts by weight of the (meth)acrylic polymer.

[0038] (Antistatic agent) As described above, in one embodiment, the pressure-sensitive adhesive layer contains an antistatic agent. As the antistatic agent, an ionic compound may be used, and preferably an ionic compound having a fluorine-containing anion is used. In addition, as the antistatic agent, an ionic surfactant, a conductive polymer, conductive fine particles, etc. may be used. The pressure-sensitive adhesive layer containing the antistatic agent can be formed, for example, by applying a conductive pressure-sensitive adhesive composition containing the pressure-sensitive adhesive and the antistatic agent by any appropriate method.

[0039] Examples of the ionic compound include inorganic cation anion salts and organic cation anion salts.

[0040] The inorganic cation anion salt may be, for example, an alkali metal salt formed from an alkali metal cation and an anion. The alkali metal salt may be an organic or inorganic salt of the alkali metal.

[0041] Examples of the alkali metal ion constituting the cation portion of the alkali metal salt include lithium, sodium and potassium ions, with the lithium ion being preferred.

[0042] The anion portion of the alkali metal salt may be composed of an organic substance or an inorganic substance. Examples of the anion portion constituting the organic salt include CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (CF3SO2)3C - , C4F9SO3 - , C3F7COO - , (CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - , PF6 - , CO3 2- , (C n F 2n+1 SO2)2N - (n is an integer from 1 to 10), CF2(C m F 2m SO2)2N - (m is an integer from 1 to 10), - O3S(CF2) l SO3 - (l is an integer from 1 to 10), (C p F 2p+1 SO2)N - (C q F 2q+1 SO2), (p and q are integers from 1 to 10), (FSO2)2N - etc.

[0043] The anion portion of the inorganic salt is Cl. - , Br - , I - , AlCl4- , Al2Cl7 - , BF4 - , PF6 - , ClO4 - , NO3 - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , (CN)2N - , etc. are used.

[0044] In one embodiment, an anion containing a fluorine atom is used. An alkali metal salt having an anion portion containing a fluorine atom is advantageous in that it has excellent ion dissociation properties.

[0045] Examples of organic salts of alkali metals include sodium acetate, sodium alginate, sodium ligninsulfonate, sodium toluenesulfonate, LiCF3SO3, Li(CF3SO2)2N, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, KO3S(CF2)3SO3K, LiO3S(CF2)3SO3K, and the like. Among these, LiCF3S O3, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, etc. are preferred, and fluorine-containing lithium imide salts such as Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(FSO2)2N, etc. are more preferred, and bis(trifluoromethanesulfonyl)imide lithium salt and bis(fluorosulfonyl)imide lithium salt are particularly preferred.

[0046] Examples of inorganic salts of alkali metals include lithium perchlorate and lithium iodide.

[0047] The organic cation anion salt is an organic salt, the cation part of which is composed of an organic substance. The anion part may be an organic substance or an inorganic substance. The organic cation anion salt may be an ionic liquid or an ionic solid.

[0048] Preferably, an ionic liquid is used as the antistatic agent. By using an ionic compound, an adhesive layer excellent in transparency and smoothness can be formed. By forming such an adhesive layer, an adhesive member with few appearance defects can be obtained. In this specification, the ionic liquid means a molten salt (organic cation anion salt) that is liquid at 40°C or less. Furthermore, it is particularly preferable that the ionic liquid has a melting point of 25°C or less.

[0049] The organic cation anion salt is composed of a cation component made of an organic substance and an anion component. Examples of the cation component include pyridinium cation, piperidinium cation, pyrrolidinium cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazolium cation, tetrahydropyrimidinium cation, dihydropyrimidinium cation, pyrazolium cation, pyrazolinium cation, tetraalkylammonium cation, trialkylsulfonium cation, and tetraalkylphosphonium cation.

[0050] Examples of the anion component include Cl. - , Br - , I - , AlCl4 - , Al2Cl7 - , BF4 - , PF6 - , ClO4 - , NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , (CN)2N - , C4F9SO3 - , C3F7COO - , ((CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3- , (C n F 2n+1 SO2)2N - (n is an integer from 1 to 10), CF2(C m F 2m SO2)2N - (m is an integer from 1 to 10), - O3S(CF2) l SO3 - (l is an integer from 1 to 10), (C p F 2p+1 SO2)N - (C q F 2q+1 SO2), (p and q are integers from 1 to 10), (FSO2)2N - etc.

[0051] In one embodiment, an anion containing a fluorine atom is used. An alkali metal salt having an anion portion containing a fluorine atom is advantageous in that it has excellent ion dissociation properties.

[0052] In one embodiment, the anion containing a fluorine atom is preferably a fluorine-containing imide anion, and more preferably a bis(trifluoromethanesulfonyl)imide anion or a bis(fluorosulfonyl)imide anion. Among them, the bis(fluorosulfonyl)imide anion is preferred. If the bis(fluorosulfonyl)imide anion is used, the desired charge amount can be achieved by adding a small amount. If the amount of the antistatic agent added is small, the thickness of the pressure-sensitive adhesive layer can be reduced, and the smoothness can be improved.

[0053] Furthermore, as the ionic compound, inorganic salts such as ammonium chloride, aluminum chloride, copper chloride, ferrous chloride, ferric chloride, and ammonium sulfate may be used.

[0054] Other antistatic agents may be used, such as ionic surfactants, conductive polymers, conductive fine particles, and other materials capable of imparting antistatic properties. Examples of ionic surfactants include various surfactants such as cationic (e.g., quaternary ammonium salt type, phosphonium salt type, sulfonium salt type, etc.), anionic (carboxylic acid type, sulfonate type, sulfate type, phosphate type, phosphite type, etc.), amphoteric (sulfobetaine type, alkylbetaine type, alkylimidazolium betaine type, etc.) and nonionic (polyhydric alcohol derivatives, β-cyclodextrin clathrate compounds, sorbitan fatty acid monoesters and diesters, polyalkylene oxide derivatives, amine oxides, etc.).

[0055] The content of the antistatic agent in the pressure-sensitive adhesive layer is preferably 0.05 to 20 parts by weight, more preferably 0.1 to 18 parts by weight, and even more preferably 1 to 16 parts by weight, relative to 100 parts by weight of the base polymer of the pressure-sensitive adhesive. If it is within such a range, a pressure-sensitive adhesive layer excellent in transparency, durability, and adhesion can be formed.

[0056] C. Conductive layer The surface resistance of the conductive layer is preferably 1×10 12 Ω / □, more preferably less than 5×10 11 Ω / □, and more preferably less than 1×10 10 Within this range, an adhesive member capable of preventing image display defects in VR goggles can be provided. The lower limit of the surface resistance of the conductive layer is, for example, 1×10 6 It is Ω / □.

[0057] Typically, the conductive layer contains an antistatic agent, which can adjust the conductivity of the conductive layer. Examples of the antistatic agent include the antistatic materials described above.

[0058] In one embodiment, the conductive layer includes a conductive polymer, which is preferably used from the viewpoints of optical properties, appearance, antistatic effect, and stability of the antistatic effect under heat and humidity.

[0059] Examples of the conductive polymer include polyaniline and polythiophene. The conductive polymer may be soluble in an organic solvent, water-soluble, or water-dispersible. A water-soluble conductive polymer or a water-dispersible conductive polymer is preferably used.

[0060] In addition, the water-soluble conductive polymer or water-dispersible conductive polymer such as polyaniline or polythiophene preferably has a hydrophilic functional group in the molecule. Examples of the hydrophilic functional group include a sulfone group, an amino group, an amide group, an imino group, a quaternary ammonium base, a hydroxyl group, a mercapto group, a hydrazino group, a carboxyl group, a sulfate ester group, a phosphate ester group, or a salt thereof. By having a hydrophilic functional group in the molecule, the water-soluble conductive polymer or water-dispersible conductive polymer can be easily prepared.

[0061] In addition, as the material for forming the anchor layer, a binder component can be added together with the conductive polymer for the purpose of improving the film forming property of the conductive polymer and the adhesion to the optical film. When the conductive polymer is a water-soluble conductive polymer or a water-dispersible conductive polymer, a water-soluble or water-dispersible binder component is used. Examples of binders include oxazoline group-containing polymers, polyurethane resins, polyester resins, acrylic resins, polyether resins, cellulose resins, polyvinyl alcohol resins, epoxy resins, polyvinylpyrrolidone, polystyrene resins, polyethylene glycol, pentaerythritol, and the like. In particular, polyurethane resins, polyester resins, and acrylic resins are preferred. One or more of these binders can be used according to the purpose.

[0062] The amounts of the antistatic agent (preferably a conductive polymer) and binder used vary depending on their types, but are preferably adjusted so that the surface resistance of the resulting conductive layer falls within the above ranges.

[0063] D. Release Liner As the release liner, for example, a release liner in which the surface of a substrate such as paper or plastic film is subjected to a release treatment such as silicone treatment or fluorosilicone treatment can be used. Examples of the substrate include olefin-based resin films such as polyethylene-based resin films, polypropylene-based resin films, and cyclic olefin-based resin (COP) films, and polyester-based films such as polyethylene terephthalate-based films. In addition, as the release liner, fluorine-based resin films such as polytetrafluoroethylene (PTFE)-based resin films, polyethylene-based resin films, polypropylene-based resin films, and olefin-based resin films such as cyclic olefin-based resin (COP) films may be used.

[0064] In one embodiment, the surface resistance of the release liner is preferably 1×10 12 Ω / □, more preferably less than 5×10 11 Ω / □, and more preferably less than 1×10 10 The surface resistivity of the release liner is preferably less than 1×10 Ω / □. By using a release liner having such electrical conductivity, it is possible to provide a pressure-sensitive adhesive member capable of preventing image display defects in VR goggles. When the release liner is made electrically conductive, the lower limit of the surface resistivity of the release liner is, for example, 1×10 6 It is Ω / □.

[0065] In one embodiment, the release liner has antistatic properties. Such a release liner contains, for example, an antistatic agent. The antistatic agent may be contained in the substrate (antistatic material-containing substrate) or the antistatic layer as a component of the release liner. Examples of the antistatic agent include the antistatic agents described above. That is, the above-mentioned ionic compounds, ionic surfactants, conductive polymers, conductive fine particles, etc. may be used. In one embodiment, the release liner contains a conductive polymer. The amount of the antistatic agent (preferably, the conductive polymer) used depends on the type of the antistatic agent, but it is preferable to adjust the amount so that the surface resistance value of the resulting release liner is within the above range.

[0066] E. Display System FIG. 3 is a schematic diagram showing a schematic configuration of a display system (VR goggles) according to one embodiment of the present invention. In FIG. 3, the arrangement and shape of each component of the display system 2 are illustrated. The display system 2 includes a display element 12, a reflecting section 14 including a reflective polarizing member, a first lens section 16, a half mirror 18, a first phase difference member 20, a second phase difference member 22, and a second lens section 24. The reflecting section 14 is disposed in front of the display surface 12a side of the display element 12, and can reflect light emitted from the display element 12. The first lens section 16 is disposed on the optical path between the display element 12 and the reflecting section 14, and the half mirror 18 is disposed between the display element 12 and the first lens section 16. The first phase difference member 20 is disposed on the optical path between the display element 12 and the half mirror 18, and the second phase difference member 22 is disposed on the optical path between the half mirror 18 and the reflecting section 14.

[0067] The display element 12 is, for example, a liquid crystal display or an organic EL display, and has a display surface 12a for displaying an image. The light emitted from the display surface 12a passes through, for example, a polarizing member (typically, a polarizing film) that may be included in the display element 12, and is converted into a first linearly polarized light.

[0068] The first phase difference member 20 is a λ / 4 member that can convert a first linearly polarized light incident on the first phase difference member 20 into a first circularly polarized light (hereinafter, the first phase difference member may be referred to as a first λ / 4 member). The first phase difference member 20 may be provided integrally with the display element 12.

[0069] The half mirror 18 transmits the light emitted from the display element 12 and reflects the light reflected by the reflecting portion 14 toward the reflecting portion 14. The half mirror 18 is provided integrally with the first lens portion 16.

[0070] The second phase difference member 22 is a λ / 4 member that can transmit the light reflected by the reflecting section 14 and the half mirror 18 through the reflecting section 14 including a reflective polarizing member (hereinafter, the second phase difference member may be referred to as a second λ / 4 member). The second phase difference member 22 may be provided integrally with the first lens section 16.

[0071] The first circularly polarized light output from the first λ / 4 member 20 passes through the half mirror 18 and the first lens unit 16, and is converted into the second linearly polarized light by the second λ / 4 member 22. The second linearly polarized light output from the second λ / 4 member 22 is reflected toward the half mirror 18 without passing through the reflective polarizing member included in the reflecting unit 14. At this time, the polarization direction of the second linearly polarized light that is incident on the reflective polarizing member included in the reflecting unit 14 is the same as the reflection axis of the reflective polarizing member. Therefore, the second linearly polarized light that is incident on the reflecting unit 14 is reflected by the reflective polarizing member.

[0072] The second linearly polarized light reflected by the reflecting unit 14 is converted into the second circularly polarized light by the second λ / 4 member 22, and the second circularly polarized light emitted from the second λ / 4 member 22 passes through the first lens unit 16 and is reflected by the half mirror 18. The circularly polarized light reflected by the half mirror 18 passes through the first lens unit 16 and is converted into the third linearly polarized light by the second λ / 4 member 22. The third linearly polarized light passes through the reflective polarizing member included in the reflecting unit 14. At this time, the polarization direction of the third linearly polarized light incident on the reflective polarizing member included in the reflecting unit 14 is the same as the transmission axis of the reflective polarizing member. Therefore, the third linearly polarized light incident on the reflecting unit 14 passes through the reflective polarizing member.

[0073] The light transmitted through the reflecting portion 14 passes through the second lens portion 24 and enters the user's eye 26.

[0074] For example, the absorption axis of the polarizing member included in the display element 12 and the reflection axis of the reflective polarizing member included in the reflection unit 14 may be arranged substantially parallel to each other or substantially perpendicular to each other. The angle formed by the absorption axis of the polarizing member included in the display element 12 and the slow axis of the first retardation member 20 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°. The angle formed by the absorption axis of the polarizing member included in the display element 12 and the slow axis of the second retardation member 22 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°.

[0075] The in-plane retardation Re(550) of the first retardation member 20 is, for example, 100 nm to 190 nm, may be 110 nm to 180 nm, may be 130 nm to 160 nm, or may be 135 nm to 155 nm.

[0076] The first retardation member 20 preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. Re(450) / Re(550) of the first retardation member 20 is, for example, less than 1, may be 0.95 or less, may further be less than 0.90, or may further be 0.85 or less. Re(450) / Re(550) of the first retardation member 20 is, for example, 0.75 or more.

[0077] The first retardation member 20 preferably exhibits a refractive index characteristic showing a relationship of nx > ny ≧ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the first retardation member 20 is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.

[0078] The first retardation member 20 is formed of any suitable material that can satisfy the above characteristics. The first retardation member 20 may be, for example, a stretched film of a resin film or an alignment cured layer of a liquid crystal compound. Note that a stretched film of a resin film may be referred to as a retardation film.

[0079] Examples of the resin contained in the resin film include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination (for example, blended or copolymerized). When the first phase difference member 20 exhibits reverse dispersion wavelength characteristics, a resin film containing a polycarbonate-based resin or a polyester carbonate-based resin (hereinafter sometimes simply referred to as a polycarbonate-based resin) may be suitably used.

[0080] As the polycarbonate-based resin, any suitable polycarbonate-based resin can be used as long as the effects of the present invention can be obtained. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of an alicyclic diol, an alicyclic dimethanol, a di-, tri- or polyethylene glycol, and an alkylene glycol or a spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol, and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used for the first phase difference member and methods for forming the first phase difference member are described in, for example, JP 2014-10291 A, JP 2014-26266 A, JP 2015-212816 A, JP 2015-212817 A, and JP 2015-212818 A, and the descriptions in these publications are incorporated herein by reference.

[0081] The above-mentioned liquid crystal compound alignment solidified layer is a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer, and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by hardening a liquid crystal monomer as described later. In the first retardation member, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the first retardation member (homogeneous alignment). Examples of rod-shaped liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable. If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it.

[0082] The alignment solidified layer of the liquid crystal compound (liquid crystal alignment solidified layer) can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.

[0083] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0084] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is polymerizable or crosslinkable, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or crosslinking treatment.

[0085] As the liquid crystal compound, any suitable liquid crystal polymer and / or liquid crystal monomer is used. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination. Specific examples of the liquid crystal compound and the method for producing the liquid crystal alignment solidified layer are described in, for example, JP 2006-163343 A, JP 2006-178389 A, and WO 2018 / 123551 A. The descriptions in these publications are incorporated herein by reference.

[0086] The thickness of the first retardation member 20 is preferably 100 μm or less. Specifically, the thickness of the first retardation member 20 made of a stretched resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, more preferably 10 μm to 60 μm, and even more preferably 20 μm to 50 μm. The thickness of the first retardation member 20 made of a liquid crystal alignment solidified layer is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and even more preferably 1 μm to 4 μm.

[0087] The in-plane retardation Re(550) of the second retardation member 22 is, for example, 100 nm to 190 nm, may be 110 nm to 180 nm, may be 130 nm to 160 nm, or may be 135 nm to 155 nm.

[0088] The second phase difference member 22 preferably exhibits an inverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the second phase difference member 22 is, for example, less than 1, and may be 0.95 or less, or may be less than 0.90, or may be 0.85 or less. The Re(450) / Re(550) of the second phase difference member 22 is, for example, 0.75 or more.

[0089] The second retardation member 22 preferably exhibits a refractive index characteristic relationship of nx > ny ≧ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the second retardation member 22 is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.

[0090] The second retardation member 22 is formed of any suitable material that can satisfy the above characteristics. The second retardation member 22 can be, for example, a stretched film of a resin film or an alignment cured layer of a liquid crystal compound. Regarding the second retardation member 22 composed of a stretched film of a resin film or an alignment cured layer of a liquid crystal compound, the same description as that of the first retardation member 20 can be applied. The first retardation member 20 and the second retardation member 22 may be members having the same configuration (forming material, thickness, optical characteristics, etc.) or members having different configurations.

[0091] The thickness of the second retardation member 22 is preferably 100 μm or less. Specifically, the thickness of the second retardation member 22 composed of a stretched film of a resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, more preferably 10 μm to 60 μm, and still more preferably 20 μm to 50 μm. Also, the thickness of the second retardation member 22 composed of a liquid crystal alignment cured layer is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and still more preferably 1 μm to 4 μm.

[0092] The reflective portion 14 may include an absorption type polarizing member in addition to the reflective type polarizing member. The absorption type polarizing member can be disposed in front of the reflective type polarizing member. The reflection axis of the reflective type polarizing member and the absorption axis of the absorption type polarizing member can be arranged substantially parallel to each other, and the transmission axis of the reflective type polarizing member and the transmission axis of the absorption type polarizing member can be arranged substantially parallel to each other. When the reflective portion 14 includes an absorption type polarizing member, the reflective portion 14 may include a laminate having a reflective type polarizing member and an absorption type polarizing member.

[0093] The reflective polarizing member can transmit polarized light (typically, linearly polarized light) parallel to its transmission axis while maintaining its polarization state, and can reflect light in other polarization states. The orthogonal transmittance (Tc) of the reflective polarizing member can be, for example, 0.01% to 3%. The single transmittance (Ts) of the reflective polarizing member can be, for example, 43% to 49%, preferably 45% to 47%. The polarization degree (P) of the reflective polarizing member can be, for example, 92% to 99.99%. The reflective polarizing member is typically composed of a film (sometimes referred to as a reflective polarizing film) having a multilayer structure. Commercially available reflective polarizing films include, for example, 3M's product names "DBEF" and "APF" and Nitto Denko's product name "APCF".

[0094] The absorptive polarizing member may typically include a resin film (sometimes referred to as an absorptive polarizing film) containing a dichroic material. The thickness of the absorptive polarizing film is, for example, 1 μm or more and 20 μm or less, and may be 2 μm or more and 15 μm or less, 12 μm or less, 10 μm or less, 8 μm or less, or 5 μm or less.

[0095] The absorptive polarizing film may be prepared from a single layer of resin film, or may be prepared using a laminate of two or more layers.

[0096] When preparing from a single-layer resin film, for example, an absorptive polarizing film can be obtained by subjecting a hydrophilic polymer film such as a polyvinyl alcohol (PVA)-based film, a partially formalized PVA-based film, or an ethylene-vinyl acetate copolymer-based partially saponified film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, a stretching treatment, etc. Among them, an absorptive polarizing film obtained by dyeing a PVA-based film with iodine and uniaxially stretching it is preferable.

[0097] The dyeing with iodine is carried out, for example, by immersing the PVA film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment or while the dyeing is being carried out. Alternatively, the stretching may be followed by dyeing. If necessary, the PVA film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like.

[0098] Examples of the laminate produced using the laminate of two or more layers include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The absorptive polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced, for example, by coating a PVA-based resin solution on the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into an absorptive polarizing film. In this embodiment, preferably, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction, thereby shrinking the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and to achieve high optical properties. At the same time, by increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of polyvinyl alcohol molecules and the decrease in the orientation can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the absorptive polarizing film obtained through treatment steps in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through drying shrinkage treatment.The obtained laminate of resin substrate / absorptive polarizing film may be used as it is (i.e., the resin substrate may be used as a protective layer for the absorptive polarizing film), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / absorptive polarizing film laminate after peeling the resin substrate from the laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such an absorptive polarizing film are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.

[0099] The crossed transmittance (Tc) of the absorptive polarizing member (absorptive polarizing film) is preferably 0.5% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. The single transmittance (Ts) of the absorptive polarizing member (absorptive polarizing film) is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the absorptive polarizing member (absorptive polarizing film) is, for example, 99.0% to 99.997%, and preferably 99.9% or more.

[0100] Each element included in a display having a display system is integrated via an adhesive layer as necessary. The adhesive layer may be formed of an adhesive or a pressure-sensitive adhesive.

[0101] In one embodiment, any one of the adhesive layers is the pressure-sensitive adhesive layer described in section B, or a laminate including the pressure-sensitive adhesive layer and the conductive layer described in section C.

[0102] 4 is a schematic cross-sectional view of an optical film with an adhesive member according to one embodiment of the present invention. The optical film with an adhesive member 200 includes an optical film A and the above-mentioned adhesive member 100 arranged on at least one side of the optical film A. The adhesive member 100 may be arranged so that the release liner 120 is on the opposite side to the optical film A. The adhesive member may be an adhesive member having a conductive layer (i.e., the adhesive member 100' shown in FIG. 2).

[0103] Any suitable optical film is used as the optical film A. Examples of the optical film A include a reflective polarizer, an absorptive polarizer, a reflective polarizing plate, an absorptive polarizing plate, and a retardation film. Examples of the reflective polarizing plate include the reflective polarizing member. Examples of the absorptive polarizing plate include the absorptive polarizing member. Examples of the retardation film include the first retardation member and the second retardation member. The optical film may be a single layer or a multilayer. In one embodiment, the outermost layer of the optical film on the adhesive member side is made of a low moisture permeable material. Examples of the low moisture permeable material include cycloolefin resins and polycarbonate resins. In the case where the adhesive member includes a pressure-sensitive adhesive layer containing an ionic liquid (for example, an ionic liquid composed of an anion containing a fluorine atom such as a bis(fluorosulfonyl)imide anion), if the outermost layer of the optical film on the adhesive member side is made of a low moisture permeable material, the penetration of the ionic liquid into the optical film can be suppressed. The moisture permeability of the low moisture permeable material at 40° C.×92% RH is, for example, 10 g / (m 2 24h)~900g / (m 2 The moisture permeability can be measured according to the JIS Z 0208 moisture permeability test (cup method).

[0104] In the manufacture of a display having a display system, the release liner is peeled off from the optical film with the adhesive member, and the optical film with the adhesive layer is attached. In this embodiment, a display with an adhesive layer is provided. By using the adhesive member according to the embodiment of the present invention, the optical film can be attached while preventing the inclusion of foreign matter. In particular, it is advantageous in that it can prevent the inclusion of even minute foreign matter.

[0105] In one embodiment, an optical film with a pressure-sensitive adhesive member is provided, which comprises an optical film including an absorptive polarizing member and the above-mentioned pressure-sensitive adhesive member. This optical film with a pressure-sensitive adhesive member can be preferably used as a polarizing member in the above-mentioned display element, for example, by removing the release liner. In this embodiment, a display element with a pressure-sensitive adhesive layer can be provided. The optical film including the absorptive polarizing member may further include a retardation film.

[0106] FIG. 5 is a schematic cross-sectional view of a lens with an adhesive member according to one embodiment of the present invention. The lens with an adhesive member 300 includes a lens B and an adhesive member 100 arranged on at least one side of the lens B. In this embodiment, a lens with an adhesive layer may be provided. The adhesive member 100 may be arranged so that the release liner 120 is on the opposite side to the lens B. The adhesive member may be an adhesive member having a conductive layer (i.e., the adhesive member 100' shown in FIG. 2). Examples of the lens B include the second lens portion and the first lens portion. EXAMPLES

[0107] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0108] [Production Example 1] (Preparation of absorptive polarizing film) A long roll of polyvinyl alcohol (PVA) resin film (manufactured by Kuraray Co., Ltd., product name "PE3000") with a thickness of 30 μm was uniaxially stretched in the longitudinal direction to 5.9 times its original size using a roll stretching machine, while simultaneously undergoing swelling, dyeing, crosslinking, and washing processes, and finally a drying process to produce an absorptive polarizing film with a thickness of 12 μm. Specifically, the film was stretched 2.2 times during the swelling treatment in pure water at 20°C. Next, the film was stretched 1.4 times during the dyeing treatment in an aqueous solution at 30°C in which the weight ratio of iodine to potassium iodide was 1:7, and the iodine concentration was adjusted so that the single transmittance of the resulting absorptive polarizing film was 45.0%. Furthermore, a two-stage crosslinking treatment was adopted, and the film was stretched 1.2 times during the first stage crosslinking treatment in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The boric acid content of the aqueous solution in the first stage crosslinking treatment was 5.0% by weight, and the potassium iodide content was 3.0% by weight. The film was stretched 1.6 times during the second stage crosslinking treatment in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The boric acid content of the aqueous solution in the second stage crosslinking treatment was 4.3% by weight, and the potassium iodide content was 5.0% by weight. The cleaning treatment was performed with an aqueous potassium iodide solution at 20° C. The aqueous solution used for the cleaning treatment had a potassium iodide content of 2.6% by weight. Finally, the film was dried at 70° C. for 5 minutes to obtain an absorptive polarizing film. (Preparation of polarizing member) A HC-attached triacetyl cellulose (TAC) resin film (TAC thickness: 25 μm, HC thickness: 7 μm) was attached to one side of the obtained absorptive polarizing film, and a cycloolefin resin film (thickness: 13 μm) was attached to the other side as a protective layer. Specifically, the curable adhesive was applied so that the total thickness was about 1 μm, and the two were laminated using a roller. Then, UV light was irradiated from the TAC film side to cure the adhesive. As a result, a polarizing member having a structure of [TAC film (protective layer) / absorptive polarizing film / COP film (protective layer)] was obtained.

[0109] [Production Example 2] (Formation of adhesive layer) A monomer mixture containing 94.9 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of 2-hydroxyethyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.3 parts by weight of dibenzoyl peroxide as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at 60°C and a polymerization reaction was carried out for 7 hours. Next, ethyl acetate was added to the resulting reaction liquid to adjust the solid concentration to 30% by weight, and a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2.2 million was prepared. An acrylic adhesive was prepared by blending 100 parts by weight of the solid content of the obtained acrylic polymer solution with 0.6 parts by weight of a trimethylolpropane / tolylene diisocyanate adduct (product name: Coronate L, manufactured by Tosoh Corporation) and 0.075 parts by weight of a silane coupling agent (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.). The obtained acrylic pressure-sensitive adhesive was applied to a substrate film, and the resulting coating film on the substrate film was dried in an oven to form a pressure-sensitive adhesive layer with a thickness of 15 μm.

[0110] [Example 1] (Preparation of Conductive Adhesive Composition) A monomer mixture containing 75 parts by weight of butyl acrylate (BA), 21 parts by weight of phenoxyethyl acrylate (PEA), 3.3 parts by weight of N-vinyl-2-pyrrolidone (NVP), 0.3 parts by weight of acrylic acid (AA), and 0.4 parts by weight of 4-hydroxybutyl acrylate (HBA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts by weight of ethyl acetate per 100 parts by weight of the monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen, and the liquid temperature in the flask was kept at around 55°C to carry out a polymerization reaction for 8 hours to prepare an acrylic polymer liquid. The acrylic polymer liquid obtained above (solid content 100 parts by weight) was mixed with 5 parts by weight of an ionic compound (organic cation anion salt (ionic liquid), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.2 parts by weight of an isocyanate crosslinking agent (Mitsui Chemicals, Takenate D160N, trimethylolpropane hexamethylene diisocyanate), 0.3 parts by weight of benzoyl peroxide (NOF Corporation, Niper BMT), and 0.3 parts by weight of a silane coupling agent (Shin-Etsu Chemical Co., Ltd.: X-41-1810) to prepare a conductive adhesive composition containing an adhesive and an antistatic agent. (Preparation of adhesive material) The above conductive adhesive composition was applied to a release liner (manufactured by Mitsubishi Chemical Polyester Film Corporation, product name "MRF38") to obtain an adhesive member consisting of a release liner and a conductive adhesive layer (thickness: 20 μm). (Preparation of Optical Films) The polarizing member obtained in Production Example 1 was laminated with the above-mentioned adhesive member so that the COP film of the polarizing member and the conductive adhesive layer faced each other to obtain an optical film with an adhesive member. A schematic diagram of the configuration of the obtained optical film with an adhesive member is shown in Table 1 together with schematic diagrams of the configurations of Examples 2 to 5 and Comparative Example (adhesive layer is not shown).

[0111] [Table 1]

[0112] [Example 2] An optical film with an adhesive member was obtained in the same manner as in Example 1, except that the amount of ionic compound (organic cation anion salt (ionic liquid), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was 0.5 parts by weight.

[0113] [Example 3] (Preparation of Conductive Layer-Forming Composition) A conductive layer-forming composition with a solids concentration of 0.5% by weight was prepared by mixing 8.6 parts by weight of a thiophene-based polymer solution (product name: Denatron P-580W, manufactured by Nagase ChemteX Corporation), 1 part by weight of a solution containing an oxazoline group-containing acrylic polymer (product name: Epocross WS-700, manufactured by Nippon Shokubai Co., Ltd.), and 90.4 parts by weight of water. The obtained conductive layer-forming coating liquid contained 0.04% by weight of the polythiophene-based polymer and 0.25% by weight of the oxazoline group-containing acrylic polymer. (Formation of conductive layer) The conductive layer-forming composition was applied to the COP film side of the polarizing member so that the thickness after drying would be 50 nm, and then dried for 2 minutes at 80° C. to form a conductive layer. The obtained conductive layer contained 8% by weight of a thiophene-based polymer and 50% by weight of an oxazoline group-containing acrylic polymer, respectively. (Preparation of adhesive material) The above-mentioned conductive layer was laminated onto a release liner (manufactured by Mitsubishi Chemical Polyester Film Corporation, product name "MRF38") via the adhesive layer obtained in Production Example 2, to obtain an adhesive member consisting of a release liner, an adhesive layer, and a conductive layer. (Preparation of Optical Films) The above-mentioned adhesive member was laminated on the polarizing member obtained in Manufacturing Example 1, with the COP film and conductive layer of the polarizing member facing each other, to obtain an optical film with adhesive member (polarizing member / adhesive member (conductive layer / adhesive layer / release liner)).

[0114] [Example 4] (Preparation of adhesive material) The adhesive layer obtained in Production Example 2 was laminated onto a conductive release liner (manufactured by Mitsubishi Chemical Polyester Film Corporation, product name "MRQ75") to obtain an adhesive member consisting of a conductive release liner and an adhesive layer (thickness: 15 μm). (Preparation of Optical Films) The above-mentioned pressure-sensitive adhesive member was laminated on the polarizing member obtained in Production Example 1 so that the COP film and the pressure-sensitive adhesive layer of the polarizing member faced each other, thereby obtaining an optical film with a pressure-sensitive adhesive member.

[0115] [Example 5] (Preparation of conductive layer) A conductive layer was obtained in the same manner as in Example 3. (Preparation of adhesive material) The above-mentioned conductive layer was laminated onto a conductive release liner (manufactured by Mitsubishi Chemical Polyester Film Corporation, product name "MRQ75") via the adhesive layer obtained in Production Example 2, to obtain an adhesive member consisting of a conductive release liner, an adhesive layer (thickness: 15 μm), and a conductive layer. (Preparation of Optical Films) The above-mentioned pressure-sensitive adhesive member was laminated on the polarizing member obtained in Production Example 1 so that the COP film and the conductive layer of the polarizing member faced each other, thereby obtaining an optical film with a pressure-sensitive adhesive member.

[0116] [Comparative Example 1] (Preparation of adhesive material) The adhesive layer obtained in Production Example 2 was laminated onto a release liner (manufactured by Mitsubishi Chemical Polyester Film Corporation, product name "MRF38") to obtain an adhesive member consisting of a release liner and an adhesive layer (thickness: 15 μm). (Preparation of Optical Films) The above-mentioned pressure-sensitive adhesive member was laminated on the polarizing member obtained in Production Example 1 so that the COP film and the pressure-sensitive adhesive layer of the polarizing member faced each other, thereby obtaining an optical film with a pressure-sensitive adhesive member.

[0117] <Foreign matter adhesion> The release liner was peeled off from the optical films with pressure-sensitive adhesive member obtained in the Examples and Comparative Examples, and the films were observed under an optical microscope (20x) to measure the number and size of foreign matter in an area of ​​20 mm x 20 mm. If the total number of foreign matter observed (total number of foreign matter with a size of 10 μm or more) was 10 or more, it was rated as × (fail), if it was 5 to 9, it was rated as ◯ (pass (preferable)), and if it was 4 or less, it was ◎ (pass (more preferable)). The release liner was peeled off at a peel angle of 180° and a pulling speed of 300 mm / min. The number of foreign matter particles attached was measured 5 minutes after the release liner was peeled off.

[0118] <Surface resistance value> The surface resistance of the element to which conductivity was imparted (the adhesive layer in Comparative Example 1) was measured using MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd. The surface resistance was measured for 10 seconds at an applied voltage of 250 V (Examples 1 and 2) or 10 V (Examples 3 to 5 and Comparative Example 1).

[0119] <Amount of charge> The release liner was peeled off from the optical film with adhesive member obtained in the examples and comparative examples, and the amount of charge of the adhesive layer and the conductive adhesive layer was measured 10 seconds after peeling. The measurement environment was 23°C and 55% RH. The peeling conditions were a peel angle of 180° and a pulling speed of 300 mm / min. The amount of charge was measured using Statiron DZ4 manufactured by Shishido Electrostatic Corporation, at a distance of 35 mm from the surface of the adhesive layer (the surface where the release liner was laminated).

[0120] <Smoothness> Using EyeScale-4W manufactured by Eye System, the level of in-plane unevenness (smoothness) of the adhesive layer was calculated as an ISC value in the ISC measurement mode of the 3CCD image sensor based on the specifications of the device. (Measurement conditions) The adhesive layer was attached to a non-alkali glass plate (Corning, 1737) and used as a sample. The light source, sample, and screen were set up in that order, and the transmitted image of the sample projected onto the screen was measured with a CCD camera. The light source and CCD camera were positioned so that the distance from the sample (adhesive layer attached to the non-alkali glass plate) was 30 cm. The light source and CCD camera were also positioned so that the distance from the screen was 100 cm. The light source and CCD camera were set up 20 cm apart so that the distance from the sample and screen was the same. The ISC value is related to the evaluation of unevenness. If the ISC value is 100 or less, unevenness can be controlled to a small extent. The smaller the ISC value, the more uniform it is. An ISC value of 50 to 100 is rated as ◯ (preferable), and 50 or less is ◎ (more preferable).

[0121] The results are shown in Table 2. [Table 2]

[0122] As is clear from Table 2, according to the embodiment of the present invention, it is possible to provide an adhesive member with little adhesion of foreign matter when peeling off the release liner. An attached optical film containing the adhesive member (adhesive member-attached optical film) can be attached to a member constituting a VR goggle (for example, a display panel) with the adhesive layer as an attachment surface. By using an adhesive member with little adhesion of foreign matter, it is possible to obtain VR goggles with reduced display defects. [Industrial Applicability]

[0123] The adhesive member according to the embodiment of the present invention can be used for a display such as VR goggles. [Explanation of symbols]

[0124] 2. Display System 12 Display element 14 Reflector 14a Reflective polarizing element 16 First lens section 18 Half Mirror 20 First phase difference member 22 Second phase difference member 24 Second lens section 100, 100' Adhesive material 110 Adhesive layer 120 Release Liner 130 Conductive layer

Claims

1. A pressure-sensitive adhesive member comprising a pressure-sensitive adhesive layer and a release liner disposed on at least one surface of the pressure-sensitive adhesive layer, the number of foreign objects on the surface of the pressure-sensitive adhesive layer when the release liner is peeled off from the pressure-sensitive adhesive member in a Class 10,000 environment as defined by Federal Standard 209D is 12 or less within a 20 mm square area; An adhesive material that is laminated to the components that make up VR goggles.

2. The pressure-sensitive adhesive member according to claim 1 , wherein the amount of charge on the surface of the pressure-sensitive adhesive layer when the release liner is peeled off in an environment of a temperature of 23° C. and a humidity of 55% Rh is less than 4.0 kV.

3. Further comprising a conductive layer; the conductive layer, the pressure-sensitive adhesive layer, and the release liner are disposed in this order. The adhesive member according to claim 1 .

4. The adhesive member according to claim 1 , wherein the adhesive layer contains an antistatic agent.

5. The adhesive member according to claim 1 , wherein the release liner contains an antistatic agent.

6. The adhesive member according to claim 3 , wherein the release liner contains an antistatic agent.

7. The adhesive member according to claim 3 , wherein the conductive layer contains an antistatic agent.

8. The adhesive member according to claim 4 , wherein the antistatic material is an ionic liquid.

9. An optical film with a pressure-sensitive adhesive member comprising the pressure-sensitive adhesive member according to claim 1 .

10. 1. A display system for displaying an image to a user, comprising: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflecting section disposed in front of the display element, the reflecting section including a reflective polarizing member and configured to reflect light emitted from the display element; a first lens portion disposed on an optical path between the display element and the reflector; a half mirror disposed between the display element and the first lens portion, the half mirror transmitting light emitted from the display element and reflecting the light reflected by the reflecting portion toward the reflecting portion; a first λ / 4 member disposed on an optical path between the display element and the half mirror; a second λ / 4 member disposed on an optical path between the half mirror and the reflecting portion; and The optical film with the pressure-sensitive adhesive member according to claim 9 is provided. Display system.

11. The display system according to claim 10 , wherein the display element comprises the optical film with the adhesive member.

12. A display comprising the display system according to claim 10 or 11.

13. A method for manufacturing a display comprising the display system according to claim 10 or 11.

14. A method for manufacturing the display according to claim 13, comprising the step of adhering the optical film with adhesive member according to claim 9.

Citation Information

Patent Citations

  • Laminate for organic el displays and circular polarizing plate used therefor

    JP2021103286A